Social media based nutrition education on changing balanced nutritional behavior to prevent anemia in adolescents - Hajrah Hajrah; Makhrajani Majid; Fitriani Umar; Rasidah Wahyuni Sari (Arsip Keilmuan Gizi (AKG), 2025)
The incidence of anemia in Enrekang Regency in 2021 was 12.2% and increased by 22.75% in 2022. This study aims to determine the effect of education using social media, such as Instagram, on changes in nutritional behavior to prevent anemia. This study employed a quasi-experimental design with a one group pretest-posttest approach. The sample used in this study were 75 female students in grades 10 and 11 at SMA Model Negeri 5 Enrekang. The sampling technique was stratified random sampling. Before being given education through social media, such as Instagram, knowledge and behavior were measured. Three days later, education was given for two weeks, and posttests 1 and 2 were conducted with a two weeks interval. Data analysis used the Wilcoxon test. The average knowledge score before being given education was 10.24 and after treatment increased by 32.7% to 13.59 in posttest 1 and posttest 2 increased by 64.4% to 16.83. The average behavioral score before education was 23.15, and after treatment, it increased to 28.53 in posttest 1 and 35.23 in posttest 2. There was an influence of education on changes in adolescents' knowledge (p=0.000) and behavior (p=0.000) regarding anemia prevention. It is recommended that education regarding the consumption of iron-rich foods and the benefits of consuming iron tablets for adolescents be provided.